Representation of Glossy Material Surface in Ventral Superior Temporal Sulcal Area of Common Marmosets - Miyakawa, Naohisa; Banno, Taku; Abe, Hiroshi; Tani, Toshiki; Suzuki, Wataru; Ichinohe, Noritaka (Frontiers in Neural Circuits, 2017)
The common marmoset (Callithrix jacchus) is one of the smallest species of primates, with high visual recognition abilities that allow them to judge the identity and quality of food and objects in their environment. To address the cortical processing of visual information related to material surface features in marmosets, we presented a set of stimuli that have identical three-dimensional shapes (bone, torus or amorphous) but different material appearances (ceramic, glass, fur, leather, metal, stone, wood, or matte) to anesthetized marmoset, and recorded multi-unit activities from an area ventral to the superior temporal sulcus (STS) using multi-shanked, and depth resolved multi-electrode array. Out of 143 visually responsive multiunits recorded from 4 animals, 29% had significant main effect only of the material, 3% only of the shape, and 43% of both the material and the shape. Furthermore, we found neuronal cluster(s), in which most cells 1) showed a significant main effect in material appearance, 2) the best stimulus was a glossy material (glass or metal), and 3) had reduced response to pixel-shuffled version of the glossy material images. The location of the gloss-selective area was in agreement with previous macaque studies, showing activation in the ventral bank of STS. Our results suggest that perception of gloss is an important ability preserved across wide range of primate species.